Production potential of crop sequences in plateau region of Bihar - Singh, M K; Thakur, R; Verma, U N; Pal, S K (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 1983-90 at Ranchi, to study the stability in production potential of 4 crop sequences; the cropping systems were maize (Zea mays L.}-wheat (Triticum aestivum L. emend, Fiori & Paol.), rice (Oryza sativa L.)-wheat, soybean [Glycine max (L.) Merr.], wheat and groundnut (Arachis hypogaea L,)-wheat.  Among the rainy-season crops the production of legumes was more stable in different years than of cereals. Wheat grown after groundnut or soybean recorded higher (15.6%) and stable yield than after maize or rice, Total production of soybean-wheat (4409 ± 598 kg/ha), groundnut-wheat (4 294 ± 678 kg/ha) and rice-Wheat (3 962 ± 681 kg/ha) was more stable than of maize-wheat (5 402 ± 1 129 kg/ha). Groundnut-wheat system was more efficient in terms of wheat-equivalent yield (6 373 kg/ha), net return (Rs 16 410/ha), benefit: cost ratio (1.87) and monetary productivity (Rs 68.38/ha/day), whereas soybean-wheat was more efficient in terms of calories (19.59 millions/ha) and protein (943 kg/ha) yield. The legume-based cropping system also improved soil-available P (191 %) and available K (54%) with minimum depletion in organic C (41 %), indicating the Significance of legume in crop sequence for sustainable production.